Eksperimen Pembelajaran Matematika dengan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) ditinjau dari Kemampuan Komunikasi Matematis Siswa Kelas IX SMP Muhammadiyah 1 Kartasura 2015/2016 - Jamilatun, Umi, Rita P. Khotimah, S. Si., M. Sc (2016)
The research aims to describe and analyze: (1) the effect of mathematics learning with Student Teams Achievement Division Strategy and Numbered Heads Together Strategy toward mathematics learning outcome, (2) the effect of student's mathematical communication ability toward mathematics learning outcome, (3) the interaction between learning strategy and student's mathematical communication ability toward mathematics outcomes. The type of the research is experiment with quasi experimental design. The population of the research was all students of IX Grade of SMP Muhammadiyah 1 Kartasura of odd semester of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methods of data collection use test, quesioner, and documentation. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect of Student Teams Achievement Division and Numbered Heads Together toward mathematics learning outcome, with F_A=4,033 (2) there is effect of student's mathematical communication ability toward mathematics learning outcome, with F_B=7,372 (3) there is no interaction between Student Teams Achievement Division based on student's mathematical communication ability toward mathematics learning outcome, with F_AB=2,855.